Tumbuhkan Semangat Kreatifitas: Strategi Membangun Budaya Inovasi Di Lingkungan Kerja - Salsabela Oktanur Ichwana; Selpi Aulia; Siti Sahariah; Ilmi Rahma Fadila; Ana Noor Andriana, S.AB., M.AB; Arwin Sanjaya, S.Pd., M.AB (Universitas Muhammadiyah Jember, 2024)
Fostering creativity and a culture of innovation in the workplace is crucial for enhancing productivity and organizational competitiveness. Creativity drives innovative solutions, while a culture of innovation supports and motivates employees. This increases employee and community satisfaction and engagement, helping organizations adapt more quickly to market and technological changes. The goal of a community service activity through a Zoom Meeting business webinar on this topic is to enhance participants' knowledge and skills in business and build an innovative workplace culture. Additionally, it aims to provide participants with practical techniques they can apply in their daily business operations, thus boosting their competitiveness and sustainability. Using both monologic and dialogic methods, the webinar showed that participants gained new perspectives on fostering creativity and innovation in the workplace, with a positive response rate of 71.4%.